THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES WITH PREMARITAL SEXUAL BEHAVIOR AT THE AR-RAHMAN REHABILITATION CENTER IN PALEMBANG CITY - Agnesia, Dwi; Jawiah, Jawiah; Pastuty, Rosyati (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Low sexual knowledge and an increase in negative sexual attitudes in Indonesia cause risky sexual behavior. This is a serious problem that causes an increase in the incidence of young pregnancies, transmission of sexually transmitted infections, and abortions. The purpose of the study was to determine the relationship between sexual knowledge and attitudes to sexual behavior at the Ar-Rahman Rehabilitation Center. This research method is a quantitative research with a cross-sectional approach. The sample was taken from the total population, namely 30 clients at the Ar-Rahman Rahabilitasi Center in Palembang City. The data analysis used was univariate analysis and bivariate analysis of the chi-square statistical test with α<0.05 and a CI of 95%. The results of the study based on the chi-square statistical test showed that there was a significant relationship between attitudes and premarital sexual behavior with p-value=0.04 and there was no relationship between knowledge and premarital sexual behavior with p-value=0.399. It is hoped that there will be cooperation between the Rehabilitation Center and health workers in providing education on premarital sexual prevention.